Legal Protection for Workers Who Do Not Receive Safety and Health Guarantees at Work - Pricillia Angellina (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The purpose of this writing is to find out how legal protection is for workers who do not get safety and health guarantees at work. This type of written research method is qualitative depending on the type of document. Qualitative research is a type of research whose results are not based on statistics or other calculations. The government and legal entities that employ workers must guarantee workers' rights in accordance with their dignity as workers, especially as human beings whose human rights are protected under Article 28 (D) of the 1945 Constitution of the Republic of Indonesia, and protect their interests. It establishes the right to legal protection for the welfare of workers and their health and safety. In fact, there are still many workers who have not received job security and BPJS Employment. Employment security and Employment BPJS are mandatory for workers if they work for the company or legal entity where they work. The government, especially companies and legal entities that employ workers, must consider the need to legally protect workers' rights in order to obtain workers' safety and social security.